PENGARUH KARAKTER EKSEKUTIF, PROFITABILITAS, SALES GROWTH DAN CORPORATE SOCIAL RESPONSBILITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - M. Qyas Aulia Rizki; Raida Fuadi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The source of state revenue that has a large contribution in financing government spending is obtained from taxes. Taxes are levies which can be imposed on taxpayers, both entities and individuals based on tax laws. This study entitled "The Influence of Executive Character, Profitability, Sales Growth, Corporate Social Responsibility (CSR) Against Tax Avoidance in Non-Financial Companies Listed on the Indonesia Stock Exchange Period 2011-2015". This study aims to determine whether the Independent variable executive character, Profitability, Sales Growth and Corporate Social Responsibility (CSR) affect Tax Avoidance as a Dependent variable. The sample of this study was 11 non-financial companies which were obtained based on the sampling criteria. The analytical method of this study uses a casual study method. The results of the study state that executive character variables, Profitability variables, Sales Growth variables and Corporate Social Responsibility (CSR) variables have a positive effect on tax avoidance or Tax Avoidance.